Measuring Corruption Tendency in Exercising Authority of the Proxy of Budget User: A Legal Culture Perspective - Sudarsana, I Made; Rahayu Gorda, AAA Ngurah Sri (Udayana Journal of Law and Culture; Vol 7 No 2 (2023)DO - 10.24843/UJLC.2023.v07.i02.p04, 2023)
Presidential Regulation No. 12 of 2021 on the Amendment to Presidential Regulation No. 16 of 2018 on Government Procurement (PR 12/2021) expands the authority for the Proxy of Budget User (PBU) to become Commitment Making Officer. Consequently, the process of procuring government goods/services is controlled by a single person; such a condition can facilitate various forms of criminal acts, especially corruption. This study aims to analyze the dual position of PBU as a Commitment Making Officer, the tendency of corruption due to the expansion of PBU’s authority, and the reformulation of PBU’s authority in the future. It is normative juridical research that examines PR 12/2021 with a qualitative analysis approach. Amendment to the Presidential Regulation on Government Procurement includes the legitimacy of PBU as a Commitment Making Officer without any requirements as stated in the previous regulation. Among others, this study underlines that centralized authority will have implications for a more robust culture of corruption due to the absence of control from other parties. In future provisions, PBU may not hold a concurrent position as Commitment Making Officer in accordance with the principles of transparency and accountability. The culture of professionalism in the procurement of government goods/services needs to be improved to reduce the culture of corruption, collusion, and nepotism.